(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article addresses relationships between scenic and social space through the reflection on two artistic experiences, in dialogue with concepts from different authors and fields of knowledge. The focused experiences include the staging of Cidade Proibida, by Cia Rústica from Porto Alegre, and a more diffuse field of experiences and practices that we identify as " cabarets of South world ". The intention is to recognize and highlight knowledge and practices of small productions in the context of scenic arts from the South of the world, which are often structured in shared constructions that subvert the imposed precariousness and invent other spaces-time in the gaps of the prevailing neoliberalism. Collective, corporeal and festive performances that collapse binarism’s and can inspire imaginaries and narratives that announce renewed futures.